Volume 1: Advances in Aerospace Technology 2014
DOI: 10.1115/imece2014-37619
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Morphing Wing Technology on Hydra Technologies Unmanned Aerial System UAS-S4

Abstract: The paper describes the application of a morphing wing technology on the wing of an Unmanned Aerial System (UAS). The morphing wing concept works by replacing a part of the rigid wing upper and lower surfaces with a flexible skin whose shape can be dynamically changed using an actuation system placed inside the wing structure. The aerodynamic coefficients are determined using the fast and robust XFOIL panel/boundary-layer codes, as the optimal displacements are calculated using an original, in-house optimisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…For the research presented in this paper, optimized airfoils were obtained for several flight cases: Mach number 0.15 and angles of attack between -3° to +3°. The new airfoil shapes were obtained using an in-house developed optimization algorithm coupled with Xfoil aerodynamic solver for estimation of the lift and drag performance of the airfoils [16,17]. Figure 4 presents an example of the shape optimization results.…”
Section: Application Of the Morphing Wing Concept On Uas-s4mentioning
confidence: 99%
“…For the research presented in this paper, optimized airfoils were obtained for several flight cases: Mach number 0.15 and angles of attack between -3° to +3°. The new airfoil shapes were obtained using an in-house developed optimization algorithm coupled with Xfoil aerodynamic solver for estimation of the lift and drag performance of the airfoils [16,17]. Figure 4 presents an example of the shape optimization results.…”
Section: Application Of the Morphing Wing Concept On Uas-s4mentioning
confidence: 99%
“…Various active and passive flow control technologies have been developed and applied in diverse practical applications [10][11][12][13][14][15][16]. Morphing technology can enhance an aircraft's performance using various parameters, including lift, drag, and flow separation control [17][18][19][20][21]. During flight, mission requirements frequently change, and aircraft often operate in less-than-ideal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Morphing optimisation has revealed that optimised lift and drag coefficients can be obtained at different flight conditions. The use of morphing wing technology as a flow control technique has resulted in efficient aerodynamic designs [15,[28][29][30]. Dynamic stall control is especially significant because it occurs in all aerospace applications, such as on UAVs [31,32], helicopter rotors [33,34], wind turbines [35,36] and military aircraft [37,38].…”
Section: Introductionmentioning
confidence: 99%